Penerapan Model Pembelajaran Cooperative Learning Tipe Jigsaw untuk Meningkatkan Keterampilan Abad 21 pada Peserta Didik Kelas E-11 SMA Negeri 6 Surakarta - Muhammad Zaki Zamani; Eny Wiji Lestari (GEADIDAKTIKA, 2025)
Communication is one of the 21st-century skills that students must have. Through good communication, students can sharpen their learning abilities. The initial communication skills of Class E-11 Students of SMA Negeri 6 Surakarta are dominated by the moderate category. Applying the cooperative learning model that allows routine communication between educators and students, students and students, and groups of students and groups of students are expected to improve students' communication skills. Data collection is done through observation and lifting. The data is presented as diagrams and then analyzed descriptively quantitatively. The results showed an increase in communication skills dominated by the % High category of 61%, Enough 28%, and Very High 11%. There are no less or low categories found. Study results also show an increase in each cycle.